The Escape from Poverty Breaking the Vicious Cycles Perpetuating Disadvantage - De Schutter, Olivier (Policy Press, 2023)
ePDF and ePUB available Open Access under CC-BY-NC-ND license. The perpetuation of poverty across generations damages lives. It weakens social cohesion and the economy and undermines environmental sustainability. This book examines why poverty is carried on from one generation to the next and what needs to be done to eradicate it. This book draws on a wide variety of sources and academic disciplines (social sciences, economics, law, community development, neuroscience and developmental psychology) along with the lived experience of people in poverty. Challenging the myths and prejudices about poverty that hinder progress, it calls for a comprehensive approach based on ensuring real equality of opportunity for all. It stresses the need to intervene early to combat child poverty and break the vicious cycles that perpetuate poverty and disadvantage.